Identification of learning sites: Presentation at CCAFS Stakeholder Workshop - Accra, Ghana - Bunn, Christian (2016)
Presentation to introduce the concept of learning sites to spark stakeholder engagement for planned further activities: Evaluate and prioritize CSA practices, conduct cost-benefit analysis, placed strategically across impact zones.